Humanoid Robot To Help Reduce Food Waste by Detecting Food Quality Using Artificial Intelligence - Khan, Sadaf Mehmood; Prasetyo, Judhi (Master Program in Mechanical Engineering, Gunadarma University, 2023)
After assessing existing problems in food wastage and identifying if any solutions pre-exist, this eventually sparked the idea for developing a solution to detect food quality and reduce food waste. This was shown by doing a thorough study in order to fully comprehend the problem of food wastage. According to the study results, the leading cause/causes of food wastage are that most family members do not complete their meal and do not check the fridge, freezer, or cabinets before going shopping. In hindsight, this preliminary study aided in the creation of a solution that might aid in the reduction of food waste by identifying the food quality of fruits and vegetables and informing the person if it can be kept or should be consumed. The solution proposed was to train Pepper, a humanoid robot, to detect the food quality of fruits and vegetables using image recognition in order to decrease food waste.